Feasibility study on sensing and prediction of backside weld geometry in cold metal transfer welding of X65 pipeline in the vertical-up position. (6th January 2023) - Chen, Zhendong; Wang, Zhijiang; Wang, Fengrui; Liang, Xinyu; Liu, Wang; Wu, Shaojie; Wang, Dongpo
Abstract: Good root-pass welding is the basic guarantee for the formation of high-performance welded joints. In the 3G (vertical) position, the difference in the directions of gravity and arc force induces the issues of uneven weld shaping and discontinuous weld penetration more serious than those in the 1G (flat) position. In order to obtain a good weld penetration state for cold metal transfer (CMT) root-pass welding in the vertical-up position, the characteristic signals that could characterize the backside weld geometry were explored, and a prediction model for the backside weld width W b was established. In this study, the topside weld pool images and the electrical signals were collected in real time. It was found that the two-dimensional topside weld pool geometrical parameters, such as weld pool area A, cannot accurately characterize the backside weld geometry. Due to the difference in arc force, the backside weld geometry with large differences can be obtained with a similar A . After the analysis of the electrical signals, the characteristic signals, namely welding heat input HI and the peak current time ratio PTR, which can represent the heat and force in the CMT welding process, respectively, were extracted, and the two were combined to establish a W b prediction model, which had a good accuracy and laid the foundation for the weld penetration control after that.